Product-Based Design Approach for Business Process Improvement: A Case Study of the SIMARSIP System at the Malang Civil Registry Office - Karina Nine Amalia; Muhammad Rafi Thufail; Oktalia Juwita (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2026)
This study investigates inefficiencies in the SIMARSIP digital archiving system used by the Malang City Civil Registry Office and proposes business process improvements by applying Root Cause Analysis (Fishbone and 5 Whys) and Product-Based Design, using qualitative data from interviews, observations, and document analysis as well as BPMN modeling and Bizagi simulation, which demonstrate that the redesigned processes reduce document submission cycle time by 50% (from 38 to 19 minutes), improve document search efficiency by 44%, enhance user flexibility through self-registration login features, and increase productivity despite reducing staff from five to four, thereby indicating that the integration of Root Cause Analysis and Product-Based Design is effective for modernizing digital public service systems.